The Role Of Primary Educational Planning in Implementing Education For Sustainale Development in Padang - Hami Mulyawan (Proceeding International Conference Of Innovation Science, Technology, Education, Children And Health, 2023)
This article aims to elaborate the role of Primary Educational planning in the level of District in implementing Education for Sustainable Development (ESD) in basic education in Padang District using the perspective of "The Whole School Approach". The analysis used in this article is qualitative approach. Using primary and secondary document analysis, this article shows us that the role of the Primary Educational planning has important effect to the success of the implementation of ESD in Padang.